Gamma Function - 5.5 Functional Relations

From testwiki
Revision as of 11:12, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
5.5.E1 Γ ( z + 1 ) = z Γ ( z ) Euler-Gamma 𝑧 1 𝑧 Euler-Gamma 𝑧 {\displaystyle{\displaystyle\Gamma\left(z+1\right)=z\Gamma\left(z\right)}}
\EulerGamma@{z+1} = z\EulerGamma@{z}
( z + 1 ) > 0 , z > 0 formulae-sequence 𝑧 1 0 𝑧 0 {\displaystyle{\displaystyle\Re(z+1)>0,\Re z>0}}
GAMMA(z + 1) = z*GAMMA(z)
Gamma[z + 1] == z*Gamma[z]
Successful Successful - Successful [Tested: 5]
5.5.E2 ψ ( z + 1 ) = ψ ( z ) + 1 z digamma 𝑧 1 digamma 𝑧 1 𝑧 {\displaystyle{\displaystyle\psi\left(z+1\right)=\psi\left(z\right)+\frac{1}{z% }}}
\digamma@{z+1} = \digamma@{z}+\frac{1}{z}

Psi(z + 1) = Psi(z)+(1)/(z)
PolyGamma[z + 1] == PolyGamma[z]+Divide[1,z]
Successful Successful - Successful [Tested: 7]
5.5.E3 Γ ( z ) Γ ( 1 - z ) = π / sin ( π z ) Euler-Gamma 𝑧 Euler-Gamma 1 𝑧 𝜋 𝜋 𝑧 {\displaystyle{\displaystyle\Gamma\left(z\right)\Gamma\left(1-z\right)=\pi/% \sin\left(\pi z\right)}}
\EulerGamma@{z}\EulerGamma@{1-z} = \pi/\sin@{\pi z}
z > 0 , ( 1 - z ) > 0 formulae-sequence 𝑧 0 1 𝑧 0 {\displaystyle{\displaystyle\Re z>0,\Re(1-z)>0}}
GAMMA(z)*GAMMA(1 - z) = Pi/sin(Pi*z)
Gamma[z]*Gamma[1 - z] == Pi/Sin[Pi*z]
Successful Successful - Successful [Tested: 1]
5.5.E4 ψ ( z ) - ψ ( 1 - z ) = - π / tan ( π z ) digamma 𝑧 digamma 1 𝑧 𝜋 𝜋 𝑧 {\displaystyle{\displaystyle\psi\left(z\right)-\psi\left(1-z\right)=-\pi/\tan% \left(\pi z\right)}}
\digamma@{z}-\digamma@{1-z} = -\pi/\tan@{\pi z}

Psi(z)- Psi(1 - z) = - Pi/tan(Pi*z)
PolyGamma[z]- PolyGamma[1 - z] == - Pi/Tan[Pi*z]
Successful Successful - Successful [Tested: 1]
5.5.E5 Γ ( 2 z ) = π - 1 / 2 2 2 z - 1 Γ ( z ) Γ ( z + 1 2 ) Euler-Gamma 2 𝑧 superscript 𝜋 1 2 superscript 2 2 𝑧 1 Euler-Gamma 𝑧 Euler-Gamma 𝑧 1 2 {\displaystyle{\displaystyle\Gamma\left(2z\right)=\pi^{-1/2}2^{2z-1}\Gamma% \left(z\right)\Gamma\left(z+\tfrac{1}{2}\right)}}
\EulerGamma@{2z} = \pi^{-1/2}2^{2z-1}\EulerGamma@{z}\EulerGamma@{z+\tfrac{1}{2}}
( 2 z ) > 0 , z > 0 , ( z + 1 2 ) > 0 formulae-sequence 2 𝑧 0 formulae-sequence 𝑧 0 𝑧 1 2 0 {\displaystyle{\displaystyle\Re(2z)>0,\Re z>0,\Re(z+\tfrac{1}{2})>0}}
GAMMA(2*z) = (Pi)^(- 1/2)* (2)^(2*z - 1)* GAMMA(z)*GAMMA(z +(1)/(2))
Gamma[2*z] == (Pi)^(- 1/2)* (2)^(2*z - 1)* Gamma[z]*Gamma[z +Divide[1,2]]
Successful Successful - Successful [Tested: 5]
5.5.E6 Γ ( n z ) = ( 2 π ) ( 1 - n ) / 2 n n z - ( 1 / 2 ) k = 0 n - 1 Γ ( z + k n ) Euler-Gamma 𝑛 𝑧 superscript 2 𝜋 1 𝑛 2 superscript 𝑛 𝑛 𝑧 1 2 superscript subscript product 𝑘 0 𝑛 1 Euler-Gamma 𝑧 𝑘 𝑛 {\displaystyle{\displaystyle\Gamma\left(nz\right)=(2\pi)^{(1-n)/2}n^{nz-(1/2)}% \prod_{k=0}^{n-1}\Gamma\left(z+\frac{k}{n}\right)}}
\EulerGamma@{nz} = (2\pi)^{(1-n)/2}n^{nz-(1/2)}\prod_{k=0}^{n-1}\EulerGamma@{z+\frac{k}{n}}

GAMMA(n*z) = (2*Pi)^((1 - n)/2)* (n)^(n*z -(1/2))* product(GAMMA(z +(k)/(n)), k = 0..n - 1)
Gamma[n*z] == (2*Pi)^((1 - n)/2)* (n)^(n*z -(1/2))* Product[Gamma[z +Divide[k,n]], {k, 0, n - 1}, GenerateConditions->None]
Failure Successful Successful [Tested: 15] Successful [Tested: 15]
5.5.E7 k = 1 n - 1 Γ ( k n ) = ( 2 π ) ( n - 1 ) / 2 n - 1 / 2 superscript subscript product 𝑘 1 𝑛 1 Euler-Gamma 𝑘 𝑛 superscript 2 𝜋 𝑛 1 2 superscript 𝑛 1 2 {\displaystyle{\displaystyle\prod_{k=1}^{n-1}\Gamma\left(\frac{k}{n}\right)=(2% \pi)^{(n-1)/2}n^{-1/2}}}
\prod_{k=1}^{n-1}\EulerGamma@{\frac{k}{n}} = (2\pi)^{(n-1)/2}n^{-1/2}

product(GAMMA((k)/(n)), k = 1..n - 1) = (2*Pi)^((n - 1)/2)* (n)^(- 1/2)
Product[Gamma[Divide[k,n]], {k, 1, n - 1}, GenerateConditions->None] == (2*Pi)^((n - 1)/2)* (n)^(- 1/2)
Failure Failure Successful [Tested: 3]
Failed [3 / 3]
Result: Indeterminate
Test Values: {Rule[n, 1]}

Result: Indeterminate
Test Values: {Rule[n, 2]}

... skip entries to safe data
5.5.E8 ψ ( 2 z ) = 1 2 ( ψ ( z ) + ψ ( z + 1 2 ) ) + ln 2 digamma 2 𝑧 1 2 digamma 𝑧 digamma 𝑧 1 2 2 {\displaystyle{\displaystyle\psi\left(2z\right)=\tfrac{1}{2}\left(\psi\left(z% \right)+\psi\left(z+\tfrac{1}{2}\right)\right)+\ln 2}}
\digamma@{2z} = \tfrac{1}{2}\left(\digamma@{z}+\digamma@{z+\tfrac{1}{2}}\right)+\ln@@{2}

Psi(2*z) = (1)/(2)*(Psi(z)+ Psi(z +(1)/(2)))+ ln(2)
PolyGamma[2*z] == Divide[1,2]*(PolyGamma[z]+ PolyGamma[z +Divide[1,2]])+ Log[2]
Successful Successful - Successful [Tested: 7]
5.5.E9 ψ ( n z ) = 1 n k = 0 n - 1 ψ ( z + k n ) + ln n digamma 𝑛 𝑧 1 𝑛 superscript subscript 𝑘 0 𝑛 1 digamma 𝑧 𝑘 𝑛 𝑛 {\displaystyle{\displaystyle\psi\left(nz\right)=\frac{1}{n}\sum_{k=0}^{n-1}% \psi\left(z+\frac{k}{n}\right)+\ln n}}
\digamma@{nz} = \frac{1}{n}\sum_{k=0}^{n-1}\digamma@{z+\frac{k}{n}}+\ln@@{n}

Psi(n*z) = (1)/(n)*sum(Psi(z +(k)/(n)), k = 0..n - 1)+ ln(n)
PolyGamma[n*z] == Divide[1,n]*Sum[PolyGamma[z +Divide[k,n]], {k, 0, n - 1}, GenerateConditions->None]+ Log[n]
Failure Successful Successful [Tested: 21] Successful [Tested: 21]